Hubungan Konsep Diri dengan Prestasi Akademik Mahasiswa Semester VIII Sekolah Tinggi Ilmu Kesehatan Aisyah Pringsewu - Triaristina, Aprilia (FKIP Universitas Lampung, 2017)
The number of samples in this study was 47 people. The results showed that. Most of the respondents who have self-concept in positive category are 31 respondents (65,9%), where there are 26 respondents (83,9%) got good academic achievement, and 5 respondents (16,1%) got poor academic achievement , And only 16 respondents (34.1%) have negative self concept, where as many as 7 respondents (43.8%) got good academic achievement, and as many as 9 respondents (56.2%) got poor academic achievement. Keywords: Self Concept, Student AchievementDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701